Development of Allexium Pterydophyta and Spermatophyta to Develop Student Identification Skills - Raida, Sulasfiana Alfi; Pujiati, Tri; Ayuningsih, Muhayadah; Amalia, Silvia Rahma; Kusumarini, Niken (Phenomenon : Jurnal Pendidikan MIPA, 2024)
The limitations of direct observation-based learning media often hinder the development of prospective teachers' identification skills. This study aims to develop students' identification skills in Allexium Pteridophyta, Bryophyta, and Spermatophyta. This developmental research uses the Borg and Gall research model. Data collection uses observation and interview sheets, questionnaires, and post-test questions on students' identification skills. The sampling technique was convenience sampling, with a population of 56 prospective teachers. The study found that the Allexium media was declared valid by experts using STEM improvements as a reference, and the media was equipped with original plant parts. The results of the practicality test based on responses from lecturers and students showed that Allexium was rated practical, with an average score of 90%. The results of the trial of use using the t-test showed that the Sig. (2 tailed) value < α (0.05), then Ha was accepted. This shows that the use of real plant parts in Allexium media is effective for students' identification skills. In further research, it is expected that the addition of plant collections and analysis of the application of question cards can be carried out so that its effectiveness in supporting the completeness of Allexium can be determined.